2019
DOI: 10.1007/s11136-019-02337-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinimetric properties of the Dutch Breast Edema Questionnaire (BrEQ-Dutch version) to diagnose the presence of breast edema in breast cancer patients

Abstract: Development and clinimetric properties of the Dutch Breast Edema Questionnaire (BrEQ-Dutch version) to diagnose the presence of breast edema in breast cancer patients Hanne Verbelen,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In order to relate our objective findings with the patients' perceptions, we selected BREAST-Q questions corresponding to breast oedema-related symptoms. Pain, heaviness, swelling and tensed skin in the breast have previously been reported in the literature [5,6,26]. The patients in this study did not report any breast oedema-related symptoms pre-or postoperatively, as indicated by the median BREAST-Q responses ranging from 1 to 2.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…In order to relate our objective findings with the patients' perceptions, we selected BREAST-Q questions corresponding to breast oedema-related symptoms. Pain, heaviness, swelling and tensed skin in the breast have previously been reported in the literature [5,6,26]. The patients in this study did not report any breast oedema-related symptoms pre-or postoperatively, as indicated by the median BREAST-Q responses ranging from 1 to 2.…”
Section: Discussionsupporting
confidence: 46%
“…Fortunately, a patient-reported questionnaire for breast oedema was recently presented and validated in a study by Verbelen et al [26]. The questionnaire focuses on patients following BCS, similar to most studies published on breast oedema [5,6,26]. A breast oedemaspecific questionnaire may be useful in future studies for assessing breasts following both breast reconstruction and BCS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are challenges with capturing physical changes associated with breast oedema, validated and reliable patient-reported outcomes are available, including a recently published breast oedema questionnaire [13][14][15]33]. Both the EORTC-Breast questionnaire and LSIDS captured the symptoms and severity of breast symptoms experienced by women and demonstrated significant reduction in symptoms.…”
Section: Discussionmentioning
confidence: 99%